2011
DOI: 10.1016/j.pain.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of neuropathic pain induced by thoracotomy: Incidence, clinical description, and diagnosis

Abstract: This study evaluated prospectively the incidence of neuropathic pain after thoracotomy, described its clinical characteristics, and delineated landmarks for its diagnosis in daily practice. We evaluated clinically painful symptoms and sensory deficits in 54 patients after lateral/posterolateral thoracotomy for broncho-pulmonary carcinoma with standardized surgical and analgesic procedures. At 2months, 49 patients suffered from non malignant thoracic pain, and at 6months 38 patients (loss to follow-up for 7) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 41 publications
6
82
3
2
Order By: Relevance
“…Overall, the rate of neuropathic pain was rather low in our study (26-28%) compared to previous studies with neuropathic rates reported to range between 40-50% (3,17,19). Again, studies were quite heterogeneous concerning patient characteristics and surgical approaches.…”
Section: Discussioncontrasting
confidence: 78%
“…Overall, the rate of neuropathic pain was rather low in our study (26-28%) compared to previous studies with neuropathic rates reported to range between 40-50% (3,17,19). Again, studies were quite heterogeneous concerning patient characteristics and surgical approaches.…”
Section: Discussioncontrasting
confidence: 78%
“…Although the median force of the stimulating monofilament in this study (255 mN) was lower than in a postmastectomy pain study 14 (1236 mN) and after a hernia repair study 13 (588 mN), it was still 25-fold higher than a previous trial on thoracotomy (9.8 mN). 7 Third, a conservative measure of temporal summation was chosen, requiring an NRS increase of >2, which could lead to an underestimation of the prevalence of temporal summation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Previous neurophysiological characterizations of postoperative nerve function after thoracotomy assessing PTPS have evaluated responses to mechanical stimuli. 5,7,11,12 These and other studies from persistent postsurgical pain states [13][14][15][16] have not managed to finally characterize persistent postsurgical pain states or have not compared pain patients to pain-free patients. Accordingly, our objective of this hypothesis-generating study was to quantitatively describe sensory changes in PTPS and painfree patients after thoracotomy using a detailed quantitative sensory testing (QST) protocol.…”
mentioning
confidence: 99%
“…Moreover, the high variability in PTPS incidence may also be explained by the different attitude of patients towards discomfort (14). patients in terms of sensory loss and hypoesthesia to cold (16,17). These neuropathic phenomena are principally located within mammary and sub mammary areas and ipsilateral scapular and interscapular regions.…”
Section: Definition and Incidencementioning
confidence: 99%